Plant commodification in Northern Mesopotamia: evidence from the Early Bronze Age site of Kani Shaie, Iraqi Kurdistan - Joka, Karolina (Frontiers in Environmental Archaeology, 2025)
One of the milestones in the trajectory of economic and social change that spurred increasing societal complexity, and urbanization was the commodification of natural resources, such as plants, animals, and their derived products. In this paper, I examine new evidence of agricultural surplus in a small-scale Early Bronze Age (dated approximately to 2900 to 2300 BCE) community at Kani Shaie in the Bazyan Valley, Iraqi Kurdistan, situating it within the broader context of early commodification and the redistribution of staple foodstuffs. Excavations at an architectural complex dated to the early phase of the EBA suggest its function as a food storage and redistribution center, supported by the presence of administrative remains (sealings), restricted access to the space, and carefully stored agricultural crops, likely intended as the basis for meals. Considering the strategic location of Kani Shaie at a junction between the mountainous Zagros region and the Mesopotamian lowlands, the site's role as a redistribution center can be analyzed within the context of mobility networks linking lowland plains and highland valleys. This contributes to the broader discussion on the role of small, remote administrative centers in the commodification of plant resources, both preceding and existing outside major centers of urbanization.